Method for improving saturation current characteristic of molded inductor

By optimizing the magnetic powder preparation process of molded inductors, including magnetic powder screening, uniform coating, multi-step granulation and fine baking, the problems of insufficient saturation current characteristics of the molded inductors, unsatisfactory magnetic powder coating effect and oxidation are solved, and higher saturation current characteristics and long-term stability are achieved.

CN120108916APending Publication Date: 2025-06-06HUNAN AEROSPACE MAGNETOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510319603.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

The saturation current characteristics of the existing molded inductors are insufficient, the magnetic powder coating effect is not ideal, the granulation process limits the improvement of the saturation current characteristics, and the oxidation problem during the baking process affects the magnetic performance.

Method used

Through magnetic powder pretreatment, uniform coating, multi-step granulation and fine baking, the magnetic powder preparation process of molded inductors is optimized. Specifically, it includes: magnetic powder screening, ultrasonic oscillation treatment of the binder acetone solution, low-speed stirring and reverse stirring to ensure uniform coating of the binder, gradually air-drying to volatile acetone, multiple screening and granulation to control particle size, and fine baking under a nitrogen environment to avoid oxidation.

Benefits of technology

It significantly improves the saturation current characteristics of the molded inductor, enhances the bonding force and molding performance of the powder, avoids oxidation of magnetic powder, and improves the mechanical strength and long-term stability of the inductor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a method for improving saturation current characteristics of a molded inductor, which comprises the following steps of: (1) screening magnetic powder to remove impurities, weighing, adding an adhesive according to a weight ratio, mixing with acetone, and performing ultrasonic oscillation to obtain an adhesive solution; (2) stirring the magnetic powder and the adhesive solution in a kneading machine at a low speed, so that the adhesive uniformly coats the surfaces of the magnetic powder particles; (3) air-drying the mixture in a temperature-controlled environment to obtain powder to be granulated; (4) granulating with a 80-mesh sieve, air-drying, and carrying out secondary humidification treatment; (5) performing air drying again, and performing granulation through a 60-mesh sieve to obtain secondary granulation powder with uniform particle size; and (6) baking under the protection of nitrogen to obtain mould pressing powder. According to the method, by optimizing coating, humidifying, granulating and baking processes, the saturation current characteristic and stability of the molded inductor are effectively improved, so that the molded inductor is more suitable for a high-current scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microbial biofilm formation methods, in particular to a method for improving the saturation current characteristics of a molded inductor. Background Art

[0002] Molded inductors are an important type of device in the field of inductor manufacturing and are widely used in power management, consumer electronics, communication equipment and other scenarios that require high current handling capabilities. Compared with traditional wound inductors, molded inductors have higher saturation current characteristics and can achieve high current loads in a smaller volume, making them the preferred solution for high-density, miniaturized inductor designs. The current mainstream molded inductors usually use a mixture of magnetic powder and adhesive for granulation, and then obtain the desired structure through molding. However, in the actual production of molded inductors, there are still the following problems that need to be solved:

[0003] Insufficient saturation current characteristics: The saturation current characteristics of molded inductors are mainly determined by the saturation magnetization intensity and particle size distribution of the magnetic powder inside them. In high current applications, the saturation current characteristics of the inductor are particularly important. The particle size distribution of the magnetic powder in the molded inductor prepared by the traditional method is relatively uneven, resulting in insufficient saturation current characteristics, which is difficult to meet the needs of higher current environments.

[0004] The magnetic powder coating effect is not ideal: In the traditional method of mixing magnetic powder and adhesive, the adhesive tends to adhere unevenly to the surface of the magnetic powder particles during the mixing process, resulting in powder stratification and loose bonding in the subsequent granulation process. These problems will cause the structural strength of the finished inductor to be insufficient after molding, affecting its long-term stability and electrical performance.

[0005] Granulation process limits saturation current characteristics: Currently, the commonly used granulation process often uses a one-time granulation method, lacks fine particle control means, resulting in a larger powder particle size. In addition, due to the lack of necessary humidification and step-by-step screening during the granulation process, it is easy to cause insufficient fine powder and cannot effectively improve the saturation current change rate of the molded inductor. Inductors produced by this process are prone to problems such as premature saturation of magnetic powder and excessive loss in high current environments, which limits the promotion of molded inductors in high current application scenarios.

[0006] Oxidation problem during baking: In the manufacturing process of traditional molded inductors, the powder after granulation is often baked directly without taking effective atmosphere protection measures, which makes the surface of magnetic powder particles easily oxidized during baking, further affecting its magnetic properties and saturation current characteristics. In addition, the traditional baking temperature control is not precise, which easily causes the adhesive to react incompletely in a high temperature environment, affecting the final performance of the molded powder.

[0007] Therefore, we designed a method to improve the saturation current characteristics of molded inductors to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to provide a method for improving the saturation current characteristics of a molded inductor in view of the shortcomings of the prior art, so as to solve the problems raised in the background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: A method for improving the saturation current characteristics of a molded inductor, comprising the following steps:

[0010] (1) Pretreatment of magnetic powder: sieving the magnetic powder to remove impurities and coarse particles to ensure uniform magnetic powder particles, weighing an appropriate amount of magnetic powder, weighing a binder at 2.0%-5.0% of the weight of the magnetic powder, and weighing acetone at 12%-30% of the weight of the magnetic powder, dissolving the binder in acetone to obtain a binder acetone solution; ultrasonic oscillation technology is used in the preparation of the binder acetone solution to improve the dissolution efficiency and dispersion uniformity of the binder;

[0011] (2) Uniform coating: The magnetic powder obtained in step (1) and the binder acetone solution are added to a kneader, and the binder is uniformly coated on the surface of the magnetic powder particles by low-speed stirring and intermittent reverse stirring to form a magnetic powder mixture with good dispersion; the stirring temperature is controlled at 30-40° C. to reduce the acetone volatilization rate and prolong the action time of the binder;

[0012] (3) Preliminary air drying: The mixed material obtained in step (2) is transferred to a material tray and air dried in a temperature-controlled environment to allow the acetone to evaporate evenly to retain the coating effect of the binder, thereby obtaining a powder to be granulated; the air drying temperature is controlled at 20-25° C. and the air humidity is controlled at about 30% to optimize the drying efficiency;

[0013] (4) First granulation: The air-dried powder is first granulated using an 80-mesh sieve to obtain a first granulated powder; a vibrating sieve is used during sieving to ensure that the powder passes through the sieve holes evenly to obtain a first granulated powder with uniform particle size;

[0014] (5) Secondary mixing and humidification: The primary granulated powder is further air-dried in a humidity-controlled environment, and after the residual acetone is volatilized, acetone equivalent to 27%-33% of the weight of the magnetic powder is added and uniformly stirred with a kneader to produce a trace secondary coating effect on the surface of the powder particles and enhance the binding force of the powder;

[0015] (6) Secondary granulation: The mixed material obtained in step (5) is air-dried and then sieved through a 60-mesh sieve for secondary granulation to obtain secondary granulated powder; in this step, the mixed material is first pre-sieved with an 80-mesh sieve and then sieved with a 60-mesh sieve to ensure the uniformity of the powder particle size and reduce the influence of coarse particles on compression molding;

[0016] (7) Fine baking: Bake the secondary granulated powder at 50-70°C for 0.5-2 hours. Fine temperature control allows the binder to react fully, avoids oxidation of the magnetic powder, and enhances saturation current performance. The baking process can be carried out in a nitrogen protection environment to reduce oxidation.

[0017] As a preferred technical solution of the present invention, the adhesive in step (1) is a modified epoxy resin, which maintains good viscosity and chemical stability in a low temperature environment and can effectively enhance the bonding force between magnetic powder particles.

[0018] As a preferred technical solution of the present invention, the air-drying process of step (3) adopts a gradual cooling method, with the initial temperature being 30°C and the temperature being reduced by 1-2°C every 5 minutes until reaching room temperature, thereby ensuring that the acetone evaporates slowly, avoiding powder agglomeration, and ensuring the uniformity of particle dispersion.

[0019] As a preferred technical solution of the present invention, the particle size of the primary granulated powder after 80-mesh screening in step (4) is controlled to be 40-60 μm, ensuring that it is suitable for compression molding of high-current inductors and effectively improving the electrical performance of the inductors.

[0020] As a preferred technical solution of the present invention, the molded powder prepared by this method has a saturation current change rate improvement of at least 3%, and has better saturation current characteristics than the molded powder prepared by the traditional granulation method.

[0021] As a preferred technical solution of the present invention, the magnetic powder particles have higher binding force after secondary granulation and baking, so that the powder is evenly distributed during the molding process, the powder stratification phenomenon during the molding process is reduced, and the mechanical strength of the inductor is improved.

[0022] As a preferred technical solution of the present invention, after the baking process of step (7) is completed, the internal stress in the powder is released by slowly cooling to room temperature, thereby improving the mechanical strength of the powder and the durability of the molded inductor.

[0023] As a preferred technical solution of the present invention, a small amount of nano-alumina is added as an auxiliary agent during the kneading process of step (2) and step (5) to enhance the surface coating effect of the magnetic powder particles and improve the anti-oxidation performance of the powder, thereby further improving the saturation current characteristics and long-term stability of the inductor.

[0024] Beneficial effects:

[0025] The present invention significantly improves the saturation current characteristics of the inductor by optimizing the magnetic powder preparation process of the molded inductor, including the particle size screening of the magnetic powder, uniform coating of the adhesive, secondary humidification treatment and precise temperature control baking steps. The improved coating and humidification process makes the adhesive distribution on the surface of the magnetic powder particles more uniform, significantly enhances the bonding force and molding performance of the powder, and overcomes the problem of electrical characteristic fluctuation caused by uneven particle coating in the traditional method.

[0026] In addition, the present invention adopts atmosphere protection during the multi-step granulation and baking process, which effectively avoids oxidation of magnetic powder and further improves the mechanical strength and long-term stability of the molded inductor. Compared with the traditional process, the molded inductor of the present invention exhibits a lower saturation current change rate and higher durability in a high current environment, laying a solid technical foundation for the wide application of molded inductors in high-power application scenarios. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The specific implementation of the present invention is described in detail below in conjunction with multiple embodiments.

[0029] The present invention provides a method for improving the saturation current characteristics of a molded inductor, which significantly improves the saturation current characteristics of the inductor by controlling the particle size of magnetic powder, the proportion of binder, environmental parameters during granulation, and baking method. The following examples describe in detail the application of the present invention under different conditions, reflecting the improvement effect of the method.

[0030] Example 1

[0031] Magnetic powder pretreatment: Weigh 200 kg of magnetic powder and sieve it using an 80-mesh sieve to remove impurities and coarse particles to ensure the consistency of the particle size of the magnetic powder.

[0032] Preparation of adhesive solution: Weigh 3.0% of the weight of the magnetic powder of modified epoxy resin adhesive, weigh 20% of the weight of the magnetic powder of acetone, and use an ultrasonic oscillator to dissolve the adhesive in acetone to obtain a uniform adhesive acetone solution.

[0033] Uniform coating: Add the magnetic powder and the binder acetone solution into a kneader, stir at a low speed at 30°C for 10 minutes, and intermittently reverse stir for 5 minutes to ensure that the binder uniformly coats the magnetic powder particles to form a mixture.

[0034] Air drying: The mixed material is transferred to a material tray and air-dried for 2 hours in an environment of 20°C and 30% relative humidity. The acetone evaporates slowly to obtain a powder to be granulated.

[0035] First granulation: The air-dried powder is granulated for the first time using an 80-mesh sieve to obtain a first granulated powder with a particle size of about 40-60 μm.

[0036] Secondary humidification: The primary granulated powder is further air-dried in a humidity-controlled environment. Then, acetone equivalent to 30% of the weight of the magnetic powder is added and stirred at room temperature by a kneader to form a secondary coating effect on the surface of the powder particles and enhance the bonding force of the powder.

[0037] Secondary granulation: After the mixed material is air-dried, it is pre-screened through an 80-mesh sieve and then shaped through a 60-mesh sieve to obtain secondary granulation powder.

[0038] Baking: The secondary granulated powder was baked at 60°C for 1 hour in a nitrogen environment and then slowly cooled to obtain a raw material powder for compression molding.

[0039] Example 2

[0040] The same steps as in Example 1 were adopted, but the binder ratio was adjusted to 2.5%, the acetone ratio was adjusted to 15%, the acetone ratio in the secondary wetting was adjusted to 27%, and the other parameters remained unchanged.

[0041] Example 3

[0042] Magnetic powder pretreatment: Weigh 300 kg of magnetic powder and sieve it to ensure uniform particle size.

[0043] Preparation of adhesive solution: Weigh 4.0% of the weight of the magnetic powder and the modified epoxy resin adhesive, with an acetone ratio of 25%, and use an ultrasonic oscillator to treat to obtain an adhesive acetone solution.

[0044] Coating and drying: The steps are the same as in Example 1.

[0045] First granulation: Use an 80-mesh sieve for granulation to obtain a primary granulation powder with a particle size between 45 and 65 microns.

[0046] Secondary wetting and granulation: The proportion of acetone in the secondary wetting was increased to 33%, and the secondary granulation step was consistent with that in Example 1.

[0047] Baking: Baking at 70°C for 0.5 hours to obtain the final powder raw material.

[0048] Comparative Example 1

[0049] Magnetic powder pretreatment: Weigh 200 kg of magnetic powder and sieve it to remove impurities.

[0050] Preparation of adhesive solution: weigh 2.5% of the weight of the magnetic powder and weigh 15% of the weight of acetone, dissolve the adhesive in acetone to obtain an adhesive acetone solution.

[0051] Uniform coating: Add the magnetic powder and the binder acetone solution into a kneader and stir at a low speed at room temperature to make the binder uniformly coat the surface of the magnetic powder to obtain a mixture.

[0052] Air drying: Transfer the mixture to a material tray and air dry it at 20°C for 1 hour to evaporate the acetone and obtain the powder to be granulated.

[0053] Primary granulation: The powder is granulated for the first time using an 80-mesh sieve to obtain a granulated powder with a particle size of about 50-70 microns.

[0054] Baking: The primary granulated powder is directly placed in an oven and baked at 60° C. for 0.5 hours without secondary wetting treatment to obtain a molding powder raw material.

[0055] Comparative Example 2

[0056] Magnetic powder pretreatment: Weigh 200 kg of magnetic powder and sieve it to remove impurities.

[0057] Preparation of adhesive solution: weigh 3.5% of the weight of the magnetic powder and weigh 20% of the weight of acetone, dissolve the adhesive in acetone to obtain an adhesive acetone solution.

[0058] Uniform coating: Add the magnetic powder and the binder acetone solution into a kneader and stir for 15 minutes at room temperature to ensure that the binder is evenly coated on the surface of the magnetic powder particles.

[0059] Air drying: Transfer the mixture to a material tray and air dry it at 20°C for 1.5 hours to evaporate the acetone and obtain the powder to be granulated.

[0060] Primary granulation: Use an 80-mesh sieve to granulate the powder once, and the particle size is controlled within the range of 50-70 microns to obtain granulated powder.

[0061] Baking: The granulated powder was directly placed in an oven and baked at 55° C. for 1 hour without secondary wetting treatment to obtain a molding powder raw material.

[0062] Test data table

[0063] The samples of Examples 1-3 and Comparative Examples 1-2 were made into 10 μH molded inductors and cured at 160° C. for 2 hours. The inductance and saturation current characteristics of the inductors were tested. The test results are shown in Table 1.

[0064] Table 1: Electrical characteristics of molded inductors of different embodiments

[0065]

[0066] It can be seen from Table 1 that, when the inductance values ​​of Examples 1-3 are basically the same, the saturation current change rates of Examples 1-3 are all increased by more than 3% compared with the control example, which proves that the technical solution of the present invention has a significant effect on improving the saturation current characteristics.

[0067] Example 4

[0068] In this embodiment, the particle size distribution of the magnetic powder is further optimized to verify the influence of different particle sizes on the electrical properties:

[0069] Magnetic powder screening: Use 80 mesh sieve and 100 mesh sieve to perform multi-layer screening on the magnetic powder, control the particle size of the magnetic powder to be between 30-50 microns, and weigh 200 kg of magnetic powder for subsequent steps.

[0070] Preparation of binder solution and secondary granulation: According to the proportion in Example 1, acetone was added after the first granulation for wetting treatment and granulation.

[0071] Baking conditions: Baking at 55°C for 1.5 hours, the results show that the electrical properties of the powder are good.

[0072] The powder prepared in this example was used to manufacture a molded inductor, and the inductor was cured at 160° C. for 2 hours. The results are shown in Table 2.

[0073] Table 2: Electrical characteristics of molded inductor of Example 4

[0074]

[0075] As can be seen from Table 2, Example 4 exhibits better performance in both inductance and saturation current characteristics, further verifying the effectiveness of optimizing the magnetic powder particle size in improving the saturation current.

[0076] This specific implementation demonstrates the application effect of the method of the present invention under different process parameter combinations, and fully illustrates the technical improvements and advantages of the present invention through data comparison of multiple embodiments and comparative examples.

[0077] The above embodiments demonstrate in detail the effects of the present invention under different process parameter conditions, fully verifying the significant effect of the method on improving the saturation current characteristics of molded inductors, and providing reliable data support for industrial applications.

[0078] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in the field. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the saturation current characteristics of a molded inductor, characterized in that: The following steps are involved: (1) Pretreatment of magnetic powder: sieving the magnetic powder to remove impurities and coarse particles, weighing an appropriate amount of magnetic powder, weighing a binder at 2.0%-5.0% of the weight of the magnetic powder, and weighing acetone at 12%-30% of the weight of the magnetic powder, dissolving the binder in acetone to obtain a binder acetone solution; ultrasonic oscillation is used in the preparation of the binder acetone solution; (2) Uniform coating: Add the magnetic powder obtained in step (1) and the binder acetone solution into a kneader, and ensure that the binder is uniformly coated on the surface of the magnetic powder particles by low-speed stirring and intermittent reverse stirring; control the stirring temperature at 30-40°C; (3) Preliminary air drying: The mixed material obtained in step (2) is transferred to a material tray and air dried in a temperature-controlled environment to allow the acetone to evaporate evenly to retain the coating effect of the binder, thereby obtaining a powder to be granulated; the air drying temperature is controlled at 20-25° C. and the air humidity is controlled at 30%; (4) First granulation: using an 80-mesh sieve to granulate the air-dried powder for the first time to obtain a primary granulated powder; (5) Secondary mixing and humidification: The primary granulated powder is further air-dried in a humidity-controlled environment, and after the residual acetone is volatilized, acetone equivalent to 27%-33% of the weight of the magnetic powder is added, and the mixture is uniformly stirred with a kneader to produce a trace secondary coating effect on the surface of the powder particles; (6) Secondary granulation: The mixed material obtained in step (5) is air-dried and then sieved through a 60-mesh sieve for secondary granulation to obtain secondary granulated powder; in this step, the mixed material is first pre-sieved with an 80-mesh sieve and then sieved with a 60-mesh sieve for forming; (7) Fine baking: The secondary granulated powder is baked at 50-70°C for 0.5-2 hours. The binder is fully reacted by fine temperature control. The baking process is carried out under nitrogen protection.

2. A method for improving the saturation current characteristics of a molded inductor according to claim 1, characterized in that: The adhesive in the step (1) is a modified epoxy resin.

3. The method for improving the saturation current characteristics of a molded inductor according to claim 1, characterized in that: The air-drying process in step (3) adopts a gradual cooling method, with the initial temperature being 30° C. and decreasing by 1-2° C. every 5 minutes until reaching room temperature.

4. The method for improving the saturation current characteristics of a molded inductor according to claim 1, characterized in that: The particle size of the primary granulated powder after 80-mesh screening in step (4) is controlled to be 40-60 μm.

5. The method for improving the saturation current characteristics of a molded inductor according to claim 1, characterized in that: The magnetic powder particles have higher binding force after secondary granulation and baking, so that the powder is evenly distributed during the molding process and the powder stratification phenomenon during the molding process is reduced.

6. The method for improving the saturation current characteristics of a molded inductor according to claim 1, characterized in that: After the baking process in step (7) is completed, the internal stress in the powder is released by slowly cooling to room temperature.

7. The method for improving the saturation current characteristics of a molded inductor according to claim 1, characterized in that: During the kneading process of step (2) and step (5), a small amount of nano-alumina is added as an auxiliary agent to enhance the surface coating effect of the magnetic powder particles.